ANALISIS PENGARUH LITERASI DIGITAL TERHADAP KEBERHASILAN TRANSFORMASI DIGITAL UMKM - Asnimar, Asnimar (Penerbit Lafadz Jaya, 2026)
This study aims to analyze the effect of digital literacy on the success of digital transformation in Micro, Small, and Medium Enterprises (MSMEs). The research employed a quantitative approach using a survey method targeting MSME owners who have adopted digital technologies in their business operations. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that digital literacy has a positive and significant effect on the success of digital transformation, with a path coefficient of 0.782 and a significance value of 0.000. The R-square value of 0.612 demonstrates that digital literacy explains 61.2% of the variance in digital transformation success. These findings confirm that MSME owners’ ability to access, understand, evaluate, and effectively utilize digital technologies plays a strategic role in improving operational efficiency, market expansion, and business competitiveness. This study highlights the importance of strengthening digital literacy as a key priority in accelerating sustainable MSME digitalization policies.